Capacity versus incentive factors explaining research productivity: Comparative and multilevel analysis of Nigeria and Ghana agricultural research systems - Ragasa, Catherine (Academic Journals, 2016)
This paper analyzes factors that explain variations in research productivity and outreach among 344 agricultural scientists in Nigeria and 237 agricultural scientists in Ghana using multilevel analysis.Education level, years of experience, and perceived adequacy of funding, physical and human resources are significant capacity actors explaining research productivity.In addition to capacity factors, incentives also showed to be significant in explaining research productivity.Reported staff satisfaction on organizational climate, presence of strong M&E system and presence of flexible-type organizational culture are consistently significant incentive factors explaining productivity.Results revealed that quantity and quality of human resources seem to be the priority for Ghana; while adequacy of physical and financial resources and implementation of organizational management systems seem to be the priority for Nigeria.